From Risk to Safety: Applying Job Safety Analysis in Organic Chemistry Practicals for Future Chemistry Educators - Dwi Ahmad Nur Ramadhani; Basil Marasinghe; Marilyn B. Castillo (Journal of Chemical Learning Innovation, 2025)
Purpose of the study: This study aims to determine the use of Job Safety Analysis in analyzing potential hazards in Organic Chemistry practicums as an effort to implement occupational safety and security for chemistry education students. Methodology: The method used is descriptive qualitative. The sample of this study was 41 students of the Chemistry Education Study Program. The instruments used were the Job Safety Analysis observation sheet and semi-structured interviews. The stages in analyzing potential hazards using the Job Safety Analysis method are (1) choosing a job, (2) determining the work steps, (3) identifying and analyzing potential hazards in each step of the work and (4) making efforts to control potential hazards. Main Findings: The results of the study showed 16 potential hazards identified using the Job Safety Analysis method. The results of the analysis of the risk level value (Risk Level) of potential hazards in all work steps divided into four stages of the practicum showed that 19% were (Extreme Risk-Very High Risk), 27% were (High Risk-High Risk), 19% were (Moderate Risk-Moderate Risk) and 35% were (Low Risk-Low Risk). Novelty/Originality of this study: This study provides an innovative contribution to the development of occupational safety culture in educational environments by integrating JSA as a preventive measure based on practical risk analysis.